Oxidative Stress, Kinase Activation, and Inflammatory Pathways Involved in Effects on Smooth Muscle Cells During Pulmonary Artery Hypertension Under Hypobaric Hypoxia Exposure - Siques, Patricia; Pena, Eduardo; Brito, Julio; El Alam, Samia (Frontiers in Physiology, 2021)
High-altitude exposure results in hypobaric hypoxia, which affects organisms by activating several mechanisms at the physiological, cellular and molecular levels and triggering the development of several pathologies. One such pathology is high-altitude pulmonary hypertension (HAPH), which is initiated through hypoxic pulmonary vasoconstriction to distribute blood to more adequately ventilated areas of the lungs. Importantly, all layers of the pulmonary artery (adventitia, smooth muscle and endothelium) contribute to or are involved in the development of HAPH. However, the principal action sites of HAPH are pulmonary artery smooth muscle cells (PASMCs), which interact with several extracellular and intracellular molecules and participate in mechanisms leading to proliferation, apoptosis and fibrosis. This review summarizes the alterations in molecular pathways related to oxidative stress, inflammation, kinase activation, and other processes that occur in PASMCs during pulmonary hypertension under hypobaric hypoxia and proposes updates to pharmacological treatments to mitigate the pathological changes in PASMCs under such conditions. In general, PASMCs exposed to hypobaric hypoxia undergo oxidative stress mediated by Nox4, inflammation mediated by increases in IL-6 levels and inflammatory cell infiltration, and activation of the protein kinase ERK1/2, which lead to the proliferation of PASMCs and contribute to the development of hypobaric hypoxia-induced pulmonary hypertension.